Thiazolidine Derivatives: An Up-to-Date Review of Synthesis and Biological Activity - Hatim, Chaimaa; Boussetta, Abdelghani; Kacem, Marieme; Dib, Mustapha; Ouchetto, Khadija; Hafid, Abderrafia; Khouili, Mostafa; Ouchetto, Hajiba (Current Topics in Medicinal Chemistry, 2025)
<span class=
Keywords: Thiazolidine